Prevalence of Congenital Malformations - Sedighah Akhavan Karbasi; Motaharah Golestan; Raziah Fallah; Fahimehsadat Mirnaseri; Kazem Barkhordari; Mahdokht Sadr Bafghee (Acta Medica Iranica, 2009)
Congenital malformation (CM) will begin to emerge as one of the major childhood health problems .Treatment and rehabilitation of children with congenital malformations are costly and complete recovery is usually impossible. The aim of this study was to determine frequency of CM in Yazd central city of the Islamic Republic of Iran to find out if there has been any difference in the rate and types of CM in this area. This descriptive-observational study carried on 4800 births delivered at all maternity hospitals in Yazd from October 2003 to June 2004. Prevalence of CM was 2.83% (2.86 % in male and 2.68 % in female) out of the 136 cases 69(51.88%) were males and 64 (48.12%) were females and 3 with ambiguous genitalia. Positive family history of CM in sibling was in only 6 cases (4.41%).Overall, musculoskeletal (0.83%), central nerv-ous system (0.47%) and genital system (0.37%) were accounted as the most common. Frequency of CM was more seen in still birth (12.5%) as in comparison to live birth (2.71%). There was not statistical difference be-tween prevalence of CM and neonatal's gender, gestational age, birth order and mother's age, drug ingestion, illness and parental consanguinity. In this study the overall prevalence of congenital malformation among the newborn was higher than those previous reported in Iran and determining the causes of this difference needs more extensive studies.